Mechanism of Rifampicin Inactivation in Nocardia farcinica. - Heba Abdelwahab; Julia S Martin Del Campo; Yumin Dai; Camelia Adly; Sohby El-Sohaimy; Pablo Sobrado (PLoS ONE, 2016)
A novel mechanism of rifampicin (Rif) resistance has recently been reported in Nocardia farcinica. This new mechanism involves the activity of rifampicin monooxygenase (RifMO), a flavin-dependent monooxygenase that catalyzes the hydroxylation of Rif, which is the first step in the degradation pathway. Recombinant RifMO was overexpressed and purified for biochemical analysis. Kinetic characterization revealed that Rif binding is necessary for effective FAD reduction. RifMO exhibits only a 3-fold coenzyme preference for NADPH over NADH. RifMO catalyzes the incorporation of a single oxygen atom forming an unstable intermediate that eventually is converted to 2'-N-hydroxy-4-oxo-Rif. Stable C4a-hydroperoxyflavin was not detected by rapid kinetics methods, which is consistent with only 30% of the activated oxygen leading to product formation. These findings represent the first reported detailed biochemical characterization of a flavin-monooxygenase involved in antibiotic resistance.